Neonatal Pneumopericardium in a Nonventilated Term Infant: A Case Report and Review of the Literature - Smita Roychoudhury; Sharandeep Kaur; Amuchou Singh Soraisham (Case Reports in Pediatrics)
Neonatal pneumopericardium (PPC) is a rare form of neonatal air leak syndrome with high morbidity and mortality. Air leak syndrome in the newborn is usually associated with active resuscitation, respiratory distress syndrome, meconium aspiration syndrome, mechanical ventilation, or trauma associated with labour. Neonatal PPC can be associated with other air leak syndromes such as pneumomediastinum, pneumothorax, pneumoperitoneum, and subcutaneous and interstitial emphysema. Spontaneous PPC is a rare event in the neonatal period. We report a case of PPC in association with pneumothorax in a nonventilated term infant. The infant responded to thoracocentesis without the need for pericardiocentesis.